Electrical conductivity and defect disorder of tantalum‐doped TiO2. Issue 9 (26th May 2017) - Alim, Mohammad A.; Bak, Tadeusz; Atanacio, Armand; Plessis, Johan Du; Zhou, Meifang; Davis, Joel; Nowotny, Janusz
Abstract: The present work reports the electrical properties of polycrystalline Ta‐doped TiO2 (0.39 at.% Ta) determined in situ at elevated temperatures (1173‐1323 K) in the gas phase of controlled oxygen activity (10 −12 Pa to 10 5 Pa). The effect of oxygen activity on the electrical conductivity and thermoelectric power of TiO2 is discussed in terms of defect disorder, including (1) the intrinsic electronic disorder that is governed by electronic compensation in the strongly reducing regime, (2) the extrinsic electronic disorder that is governed by electronic charge compensation in the reducing regime, and (3) the extrinsic ionic disorder that is governed by ionic compensation in the oxidizing regime. It is shown that tantalum ions are incorporated into the titanium sublattice of TiO2 leading to the formation of donor‐type energy levels. The Arrhenius‐type plot of the electrical conductivity data leads to the determination of the formation enthalpy terms. The obtained results are considered in terms of the effect of tantalum and oxygen activity on the defect disorder and the associated key performance‐related properties in the light‐induced partial water oxidation.